Structural models of amorphous silicon surfaces - Hadjisavvas, George C.; Kopidakis, Georgios; Kelires, Pantelis C. (My University, 2001)
Using Monte Carlo simulations within the empirical potential approach, we predict and analyze possible models of the surface structure of amorphous silicon. This is a fundamental problem about which knowledge is incomplete. We address the central question regarding the dominant type of nontetrahedral atoms at the surface. Our investigations lead to two markedly different models of the surface structure. One of the models exhibits a surface layer terminated by threefold- and fourfold-coordinated atoms. In general, threefold atoms are on top and form mostly dimers and chainlike structures. The other model requires that the surface is terminated by fourfold atoms and by fivefold atoms assembled in clusters of pyramidal shape, with both types of geometries heavily distorted. We also use the tight-binding method to calculate the electronic density of states of these two possible models. The electronic fingerprints of the nontetrahedral atoms within and near the energy gap region are quite different. This distinguishes clearly the two models and could guide experimental work to infer the microscopic picture of clean amorphous silicon surfaces.
Keywords: Geometry; Silicon; Mathematical analysis; Electron; System analysis